2016
DOI: 10.1038/srep36666
|View full text |Cite
|
Sign up to set email alerts
|

Composition of gut microbiota in infants in China and global comparison

Abstract: Symbiotic gut microbiota is essential for human health, and its compositional changes have been associated with various complex disorders. However, systematic investigation of the acquisition and development of gut microbial communities during early infancy are relatively rare, particularly for infants from non-Western countries. In this study, we characterize the colonization and development of infant microbiota in healthy Chinese infants and compare the pattern with those from other countries. The fecal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 41 publications
6
42
0
2
Order By: Relevance
“…Most infants from western countries are A-type, with 82% of American, 79% of Canadian, and 54% of Swedish infants being A-type, whereas most of those in Bangladeshi (70%) are F-type (Kuang et al, 2016). It has been reported that Chinese infants (age < 3 months) are predominately P-type (Kuang et al, 2016). Consistently, our data also demonstrated that Chinese infants aged 0-3 months were dominated by Proteobacteria.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Most infants from western countries are A-type, with 82% of American, 79% of Canadian, and 54% of Swedish infants being A-type, whereas most of those in Bangladeshi (70%) are F-type (Kuang et al, 2016). It has been reported that Chinese infants (age < 3 months) are predominately P-type (Kuang et al, 2016). Consistently, our data also demonstrated that Chinese infants aged 0-3 months were dominated by Proteobacteria.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the gut microbiome of C-section-delivered infants is similar to the mothers' skin microbiome, which has predominately Staphylococcus (phylum Firmicutes), Corynebacterium (phylum Actinobacteria), and Propionibacterium (phylum Actinobacteria) (Dominguez-Bello et al, 2010). A previous study of Chinese newborns (neonates and 2-month-olds) showed that vaginal delivery results in an enrichment of Bacteroides, Parabacteroides, and Megamonas, whereas C-section delivery led to an enrichment of Prevotella, Streptococcus, and Trabulsiella (Kuang et al, 2016). It is worth noting that Prevotella, which are enriched in vaginally delivered Amerindian infants (Dominguez-Bello et al, 2010), are also found in C-section-delivered Chinese infants (Kuang et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Streptococcus was more abundant in the gut microbiome of CS-delivered neonates 25-40 h after delivery than in that of vaginally delivered neonates (relative abundance 12 vs. 1%, respectively) [22]. Analysis of the gut microbiome of neonates in China 2-3 days after birth showed that Streptococcus accounted for 3% of the relative abundance in vaginally delivered neonates compared with 17% in CS-delivered neonates [23]. Because Streptococcus is frequently detected on human skin [24], CS-delivered neonates are thought to acquire Streptococcus more readily than vaginally delivered neonates because they have more contact with adults including medical staff.…”
Section: Discussion/conclusionmentioning
confidence: 97%